Strategy Analysis for Improving Product Quality in the Choque Chocolate Business in Koto Tuo IV Koto, Agam Regency - Hardianti, Windi; Asyari, Asyari (Journal of Islamic Economics and Business, 2024)
This study aims to identify strategies for enhancing product quality in the Choque chocolate business in Koto Tuo IV Koto, Agam Regency. Using a descriptive qualitative approach and SWOT analysis, data were collected through interviews, observations, and documentation. The findings show that improving product quality positively impacts product durability and consumer purchasing power. Recommended strategies include enhancing flavor variety, leveraging social media for marketing, collaborating with delivery services, optimizing production processes, and aligning production with demand. These strategies aim to increase competitiveness and meet consumer expectations effectively.